Prognostic significance of elevated platelet count (> 200 x 10^9 per L) in BCLC stages B and C of hepatocellular carcinoma: a retrospective multicenter analysis - Munker, Stefan; Rodriguez, Isaac; Bernhart, Kathrin; Khaled, Najib Ben; Findik, Merve; Siegmund, Lisa Katrin; Ye, Liangtao; Reiter, Florian P.; Roessler, Daniel; Nasseh, Daniel; Balcar, Lorenz; Pomej, Katharina; et al. (Journal of hepatocellular carcinoma, 2025)
Evaluating the prognostic role of platelet counts across BCLC stages, adjusted for portal hypertension, to improve individualized patient management with HCC
Im Titel werden das "Größer als"-Symbol und das Zirkumflex als Potenzzeichen verwendet
Im Titel ist das Potenzzeichen hochgestellt
Gesehen am 12.08.2025